Nicotine-induced CHRNA5 activation modulates CES1 expression, impacting head and neck squamous cell carcinoma recurrence and metastasis via MEK/ERK pathway - Chen Feng; Wei Mao; Chenyang Yuan; Pin Dong; Yuying Liu (Cell Death and Disease)
Abstract The mucosal epithelium of the head and neck region (including the oral cavity, nasal cavity, pharynx, nasopharynx, and larynx) is the primary site exposed to tobacco smoke, and its presence of nicotinic acetylcholine receptors (nAChRs) has been observed in the mucosal epithelial cells of this area. It remains unclear whether HNSC cells can migrate and invade through nAChR signaling. A model of HNSC cells exposed to nicotine is established. Cell proliferation following nicotine exposure is assessed using the CCK-8 assay, while migration and invasion are evaluated through wound healing and Transwell assays. The effects of CHRNA5 knockdown and overexpression are also investigated. Immunofluorescence staining is used to analyze CHRNA5 expression and localization, and clonogenic assays are performed to measure colony proliferation after CHRNA5 knockdown and overexpression. The interaction between CHRNA5 and CES1 is examined using molecular docking, co-immunoprecipitation, and immunofluorescence. Differentially expressed genes are subjected to pathway enrichment analysis, and MEK/ERK protein expression and phosphorylation are validated via western blot. Tumor formation assays are performed in nude mice using sh-CHRNA5 Cal27 cells, followed by western blot and immunohistochemical staining. Additionally, laryngeal and hypopharyngeal cancer tissues are analyzed through immunohistochemistry. Nicotine significantly enhanced the proliferation, migration, and invasion capabilities of head and neck tumor cells, including Cal27, Fadu, HN6, and Tu686 cells, through the expression of CHRNA5. Knockdown of CHRNA5 can reduce cell migration, invasion, and proliferation, whereas nicotine exposure can reverse this trend. Additionally, the mRNA and protein expression of CES1 decreases with the knockdown of CHRNA5, indicating a regulatory relationship between the two. Transcriptomics revealed that the knockdown of CHRNA5 is associated with the MEK/ERK signaling pathway. Further cellular- and tissue-level evidence confirmed that the levels of p-MEK/MEK, p-ERK/ERK, and CES1 decreased following knockdown of CHRNA5, a trend that nicotine can reverse. Nicotine promotes the proliferation, migration, and invasion of HNSC by upregulating CHRNA5 expression. Knockdown of CHRNA5 reduces these effects, which can be reversed by nicotine. Nicotine exposure activates CHRNA5, regulating CES1 expression via the MEK/ERK pathway, contributing to the recurrence and metastasis of head and neck squamous carcinoma.